The Structure and Composition of a Tropical Dry Forest Landscape After Land Clearance : Azuero Peninsula, Panama - Griscom, H.P.; Connelly, A.B.; Ashton, M.S.; Wishnie, M.H.; Deago, J. (Taylor and Francis, 2013)
Characterization of preexisting flora is an essential preliminary step for successful land rehabilitation projects. This descriptive study was undertaken in a fragmented, dry tropical forest region in Panama. Five different habitat types were selected: active pasture, 2-yr and 5-yr abandoned pastures, forested riparian zones, and a forest fragment. Species richness, density, basal area, dispersal modes, and phenology of trees as well as their uses were determined. Diversity of preexisting seed resources as well as natural regeneration was poor after 2- and 5-yr postcattle removal, suggesting that at an early successional stage, enrichment planting is necessary. Guazuma ulmifolia and Cordia alliodora dominated the pastoral landscape, representing 63% of all inventoried trees in the active pasture. More than half the trees within pastures (76%) had some use, with shade for cattle as the most common reason for leaving trees in the landscape. The largest trees and the greatest diversity were found within the less managed forested riparian zones because of inaccessibility and water conservation. The pastoral landscape is largely shaped by farm management as well as ecological selection process which will in turn affect successional processes.